2014
DOI: 10.1515/itit-2014-1048
|View full text |Cite
|
Sign up to set email alerts
|

Tweets vs. Mendeley readers: How do these two social media metrics differ?

Abstract: A set of 1.4 million biomedical papers was analyzed with regards to how often articles are mentioned on Twitter or saved by users on Mendeley. While Twitter is a microblogging platform used by a general audience to distribute information, Mendeley is a reference manager targeted at an academic user group to organize scholarly literature. Both platforms are used as sources for so-called "altmetrics" to measure a new kind of research impact. This analysis shows in how far they differ and compare to traditional c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
117
3
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
9
1

Relationship

8
2

Authors

Journals

citations
Cited by 130 publications
(129 citation statements)
references
References 17 publications
7
117
3
2
Order By: Relevance
“…Of the various alternative indicators (altmetrics) that have been proposed, Mendeley reader counts are the most promising for early impact evidence because of their relatively high correlations with citation counts and early appearance (Zahedi, Costas, & Wouters, 2014). Although tweets may appear sooner, they are much less reliable for impact indicators (Haustein, Larivière, Thelwall, Amyot, & Peters, 2014;Thelwall, Haustein, Larivière, & Sugimoto, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Of the various alternative indicators (altmetrics) that have been proposed, Mendeley reader counts are the most promising for early impact evidence because of their relatively high correlations with citation counts and early appearance (Zahedi, Costas, & Wouters, 2014). Although tweets may appear sooner, they are much less reliable for impact indicators (Haustein, Larivière, Thelwall, Amyot, & Peters, 2014;Thelwall, Haustein, Larivière, & Sugimoto, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that counts of Mendeley readers correlate with citation counts for individual journal articles within a field, whichever field is analysed (Bar-Ilan, 2012;Haustein, Larivière, Thelwall, Amyot, & Peters, 2014;Li, Thelwall, & Giustini, 2012;Thelwall, & Wilson, in press;Zahedi, Costas, & Wouters, 2014). Mendeley users tend to be younger than average and include a small proportion of master's and bachelor's degree students (less than 20% -perhaps much less due to ambiguity in Mendeley's user category names) that presumably do not publish, as well as professional users such as medical doctors and librarians (Mohammadi, Thelwall, Haustein, & Larivière, in press).…”
Section: Introductionmentioning
confidence: 99%
“…Social media, especially Twitter, is increasingly used as a way of demonstrating impact in biomedicine. Haustein (21) reported that 20 % articles indexed in PubMed in 2012 received at last one tweet. This finding raises the question as to whether an OA paper which scores high on altmetrics tools actually gets much higher download and citation rates compared to a paper with a low altmetrics score.…”
Section: Debates and Controversies About The Impact Of Open Accessmentioning
confidence: 99%